Adopting a "Both/And" Mindset to Address Relationship Violence and Sexual Misconduct (RVSM) in Institutions of Higher Education. (January 2023) - Campbell, Rebecca; Moylan, Carrie A.; PettyJohn, Morgan E.; Munford, Andrea; Schweda, Kelly; Fedewa, Tana; Rosen, Holly; Ferguson, Mary Ann; Beal, Jesse; Buchanan, NiCole T.
Michigan State University (MSU) created a long-term, values-based strategic plan to increase help-seeking and reduce the incidence of relationship violence and sexual misconduct. Creating systemic change in institutions of higher education is challenging, particularly so in the wake of massive institutional crises and betrayal, as we had at MSU. In this paper, we address the challenges and critiques of our strategic planning efforts offered by esteemed scholar-activists: Jacobson López (2023), Hirsch and Khan (2023), McMahon (2023), and Boots et al. (2023).